Caracterizacion morfologica de 13 variedades de arroz venezolanas - Montoya, M.=700 1 Rodriguez, N.; Perez Almeida, I.; Cova, J.; Aleman, L.
(Es, En)
ilus., 15 ref.
Keywords: ORYZA SATIVA; ANATOMIA DE LA PLANTA; CARACTERISTICAS AGRONOMICAS; VARIEDADES; VENEZUELA; AGRONOMIA TROPICAL